A facile method for vancomycin C-terminus functionalization and derivatization through hydrazide. (15th June 2021) - Hu, Yu; Zou, Xiangman; Shi, Weiwei; Ma, Chenhui; Chen, Feifei; Li, Jian; Jiao, Shang; Pan, Guoyu; Lan, Lefu; Huang, Wei; Tang, Feng; Zhang, Fan
Graphical abstract: Abstract: Over 60-year clinical use of vancomycin led to the emergence of vancomycin-resistant bacteria and threatened our health. To combat vancomycin-resistant strains, numerous vancomycin analogues were developed, such as Telavancin, Oritavancin and Dalbavancin. Extra structures embedded on C-terminus has been proved to be an effective strategy to promote antibacterial activity of vancomycin against vancomycin-resistant strains. Here, we reported a facile strategy, inspired by native chemical ligation, for vancomycin C-terminus functionalization and derivatization. The introduction of C-terminal hydrazide on vancomycin not only provided us an accessible method for C-terminus functionalization through carbonyl azide and thioester, also acted as an efficient site for vancomycin structure modifications. Based on hydrazide-vancomycin, we effectively conjugated cysteine and cysteine containing peptides onto vancomycin C-terminus, and two fluorescent FITC-vancomycin were prepared through Cys-Maleimide conjugation. Meanwhile, we introduced lipophilic structures onto vancomycin C-terminus via the hydrazide moiety. The obtained vancomycin derivatives were evaluated against both Gram-positive and negative bacteria strains.